The Role of Information Technology In Public Safety Development Strategy For The Activity Service Information System (SIAP) Application In Agribusiness Services - Nitam Kasim; Supriyo Imran; Asda Rauf; Abdul Fajar Haras (Citakonsultindo, 2026)
The utilization of information technology is a key factor in improving the efficiency and transparency of services in the agribusiness sector. This study aims to formulate a development strategy for the Service Activity Information System (SIAP) application to optimize service quality for stakeholders. The research method used is qualitative descriptive with the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis instrument. The results indicate that the SIAP application is positioned in Quadrant I (Progressive Strategy) on the SWOT matrix, suggesting that the organization possesses significant internal strengths and substantial external opportunities for expansion. Based on this positioning, the study recommends two primary strategies first Intensive Digitalization-Based Service Expansion which focuses on developing more diverse and user-friendly service features to reach a broader user base, Second Strengthening Legitimacy through the Integration of the One Data Policy, to ensure information synchronization and data validity across all levels of agribusiness administration.